How important are exports and foreign direct investment for economic growth in the People's Republic of China? - Yuqing Xing; Manisha Pradhananga (Asian Development Bank Institute (ADBI), 2013)
The global financial crisis and the recent growth slowdown in the People's Republic of China (PRC) have led to questions about the sustainability of the PRC's growth. The commonly used argument is that the PRC is too dependent on external demand and that it needs to rebalance its economy toward domestic consumption. However, conventional measures of external demand - share of net exports and exports as a share of gross domestic product (GDP) - are biased and do not accurately measure the contribution of external demand to GDP growth. In this paper, the authors propose two measures that provide a more accurate estimate of the vulnerability of the PRC economy to external shocks, in the form of sudden drops in exports and foreign direct investment (FDI). Based on their findings, the authors conclude that the PRC economy remains highly dependent on external demand in the form of exports and FDI, and rebalancing the economy toward domestic demand has not yet been achieved.
Keywords: F43; E01; 330; prc economy; growth; external demand; gdp accounting; Export; Auslandsinvestition; Wirtschaftswachstum; China